Are Social Enterprises Efficient? A Theoretical Approach1. Issue 4 (7th October 2018) - Beckmann, Tobias
Abstract : Social enterprises are increasingly being used to distribute income to disadvantaged groups. However, a lack of consensus of what a social enterprise is has prevented researchers from assessing their relative allocative efficiency. I address this gap by extending the standard microeconomic model of a profit‐maximising firm to consider social enterprises as a Social Corporation (SC). I then analyse four types of SC, showing that three can be as allocatively efficient as a for‐profit firm in equilibrium, despite inputs not necessarily being paid their marginal benefit.